1990
DOI: 10.1111/j.1460-9568.1990.tb00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Putative Transmitter Phenotypes and Connectivity of Subplate Neurons During Cerebral Cortical Development

Abstract: During development, the earliest generated neurons of the mammalian telencephalon reside in a region of the white matter, the subplate, just beneath the cortical plate. Neurons in the subplate are only transiently present in the telencephalon: shortly after birth in the cat the majority have disappeared. During their brief life, however, subplate neurons mature; they extend long-distance and local projections, and express immunoreactivity for GABA and several neuropeptides. In the present study we examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 73 publications
(117 reference statements)
4
61
0
Order By: Relevance
“…Both electrophysiological properties and cell morphology point to a high degree of underlying diversity among subplate neurons (Antonini & Shatz, 1990;Hanganu et al 2001;Hoerder, 2007). There are two basic classes of neuronal phenotypes in the subplate, glutamatergic and c-aminobutyric acid (GABA)ergic (Antonini & Shatz, 1990;Meinecke & Rakic, 1992), with each class expressing heterogeneous molecular markers (Allendoerfer & Shatz, 1994;Hevner & Zecevic, 2006;Hoerder-Suabedissen et al 2009). It is not yet clear whether the same types of subplate neurons possess intracortical and extracortical projections and how the diverse somatodendritic morphologies relate to the equally diverse neurochemical properties and physiological fingerprints.…”
Section: Multiple Functions Of Subplate Neurons During Cortical Develmentioning
confidence: 99%
“…Both electrophysiological properties and cell morphology point to a high degree of underlying diversity among subplate neurons (Antonini & Shatz, 1990;Hanganu et al 2001;Hoerder, 2007). There are two basic classes of neuronal phenotypes in the subplate, glutamatergic and c-aminobutyric acid (GABA)ergic (Antonini & Shatz, 1990;Meinecke & Rakic, 1992), with each class expressing heterogeneous molecular markers (Allendoerfer & Shatz, 1994;Hevner & Zecevic, 2006;Hoerder-Suabedissen et al 2009). It is not yet clear whether the same types of subplate neurons possess intracortical and extracortical projections and how the diverse somatodendritic morphologies relate to the equally diverse neurochemical properties and physiological fingerprints.…”
Section: Multiple Functions Of Subplate Neurons During Cortical Develmentioning
confidence: 99%
“…Moreover, recent evidence has shown that certain transient neuronal populations are essential for the formation of neural networks by providing guiding and targeting cues necessary for the establishment of the axon pathway. Striking examples of such a role are the subplate neuronal population of the developing cerebral cortex, which is essential for the formation of appropriate thalamocortical relationships (Shatz, 1992;Antonini and Shatz, 1990;McConnell et al, 1989;Luskin and Shatz, 1985). and the many examples of guidepost cells in invertebrates (Palka et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…A second type of SPi-positive neuron had an inverted pyramidal-shaped cell body and dendritic spines. Similar types of inverted pyramidal subplate neurons project to the thalamus and can be labeled by the retrograde transport of [3H]aspartate (40). In addition, Golgi impregnation or intracellular staining ofkitten cortical subplate neurons with biocytin has revealed some subplate neurons with typical pyramidal or bipolar cell bodies (30).…”
Section: Resultsmentioning
confidence: 99%